Liveworksheet-Based Student Worksheet for Senior High School in Physics Learning - Harmita, Putri Lingga; Dewi, Wahyuni Satria; Akmam, Akmam; Hidayati, Hidayati (Universitas Islam Negeri Raden Intan Lampung, 2023)
Physics learning should be equipped with technology-assisted student worksheets following the demands of the 2013 curriculum and contain steps in the scientific approach. This study aimed to produce electronic student worksheets based on liveworksheets on sound waves. This research is development research using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. This research was conducted in a school in Salimpaung. Data collection is based on product validation and trial results. The data analysis technique used is descriptive statistics. The validation results of the three validators who rated it gave an average score of 87.4% in the